IMPACT OF ILLEGAL GOLD MINING IN JAMBI, INDONESIA - Wibowo, Yudha Gusti; Ramadan, Bimastyaji Surya; Maryani, Anis Tatik; Rosarina, Desy; Arkham, La Ode (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2022)
Illegal gold mining caused various environmental damages in the world. Indonesia is one of the countries with abundant mineral reserves, especially Jambi Province. Jambi has much of natural resources, such as coal and gold. Unfortunately, the management of these natural resources has not been appropriately managed, which has resulted in much illegal gold mining. Illegal mining activities have caused environmental damage, mainly decreased water quality and changed landscapes. This paper explains the illegal mining activities at Jambi Province, including its history, socio-economic and environmental impacts, as well as recent technologies to reduce the environmental damage. Quantitative and qualitative methods were used in this research, including interviews, questionnaires, and laboratory measurements. The results showed that the people of Sarolangun, Bungo, and Tebo were aware that their illegal gold mining activities caused environmental damage. However, economic conditions and insufficient employment opportunities made unlawful gold miners have no other choice. Illegal gold mining activities have also shifted people's livelihoods who previously worked as farmers.